(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Pedagogy is a science that deals with the study of principles and methods, according to which the instructive-educational process (teaching) is developed, namely it is a science that deals with the study of education and training in the broader plan (in educational institutions, sports, etc. ), as well as the methods used for this purpose.Otherwise, it is a teaching subject, namely a book, a text that provides general or special knowledge from pedagogy, which provides knowledge about the methods and principles of pedagogy work. Didactics studies the structuring of learning content, the flow of the cognitive process, the main factors of learning, didactic laws, types and systems of learning, learning planning, learning excursions, principles, methods, learning forms and instruments, the learning plan and program. The history of pedagogy (and education) deals with the study of the presentation and development of education, education and pedagogical thought in the past of human society, starting from the most distant past to its most recent past. School pedagogy is primarily related to pedagogical sciences, especially didactics, general pedagogy, comparative pedagogy, etc. A teacher is a Pedagogy professional who has the ability to educate his/her students and guide them in various subjects.